TRENDS OF IMPLEMENTATION OF RESEARCH-EXPERIMENTAL ACTIVITIES IN PRESCHOOL EDUCATIONAL INSTITUTIONS OF UKRAINE IN TODAY’S CONDITIONS - Karuk, Inna; Kolesnik, Kateryna; Kryvosheya, Tetiana; Pakhalchuk, Natalia; Pokhyla, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article characterizes the current state of implementation of children’s experimentation in preschool pedagogy of Ukraine. The results of a survey of pedagogues of preschool educational institutions regarding the peculiarities of the organization and implementation of the functions of research-experimental activities of preschoolers have been given. The authors carried out definitive analysis of the concepts of the research «children's experimentation», «research-experimental activity». The content and features of the organization of research-experimental activities of preschool children have been clarified, taking into account the psychological-pedagogical publications of modern foreign and Ukrainian scientists and the available creative pedagogical experience. Examples of researches and experiments for preschool children have been offered. Materials and methods. Theoretical (analysis and synthesis of scientific sources, generalization and systematization) and empirical methods (survey) have been used in the process of research. The authors conducted a questionnaire in order to find out the state of the organization of children’s experimentation in preschool educational institutions. Results. As a result of the research, it is established that almost the third of the respondents are afraid to change the traditional system of preschool education, namely the transfer of «ready-made» knowledge to children, which becomes the main obstacle to the introduction of experimentation into educational practice. Conclusions. Based on the analysis of pedagogues’ surveys, the study of theoretical and practical experience, trends of implementation of children’s experimentation in preschool educational institutions in today’s conditions have been determined.